Artificial Intelligence Applied to Business: Case Studies and Implications - Segura, Mauro (Journal of Sustainable Competitive Intelligence, 2018)
Objective: This study aims to analyze the implementation of Artificial Intelligence (AI) in Brazilian business environments, focusing on how organizations can enhance operations through AI technologies. Method: The research adopts a case study methodology, examining several examples of AI applications in diverse industries, including banking, education, and legal services. The study assesses the impact of AI-driven solutions on operational efficiency and customer service. Results: AI technologies, such as chatbots and cognitive computing, have significantly improved service quality and operational performance across various sectors. For example, Bradesco's BIA and MRV Engenharia’s Maria Rosa demonstrate how AI can streamline customer service and internal processes, achieving higher precision and reduced response times. The study highlights the importance of carefully tailored AI solutions to meet specific organizational needs. Conclusion: AI has proven to be a transformative tool for businesses, enhancing efficiency and improving customer interaction. However, successful AI adoption depends on strategic implementation, ensuring that solutions are designed to address specific business challenges. Organizations that invest in AI can expect improved operational capabilities and competitive advantages in their respective industries.